TRAVEL GUIDEBOOK HANG AROUND DESTINASI PADANG - ADITYA PUTRA ERSANTA, Drs. Ir. Heldi, M.Si., Ph.D., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The city of Padang, the city known through the legends of Siti Nurbaya and Malin Kundang has a variety of tourist options, ranging from history, nature, culinary, religious and shopping. However, the lack of information and media regarding the tourism of Padang City made several tourist attractions in the city of Padang not yet known by many people. The book Hang Around Padang Travel Guide contains about popular tourist destinations in the city of Padang. This book uses interesting photography so that the information delivered is easy to understand. The purpose of designing this book is to promote tourism in the city of Padang. So that people outside West Sumatra can find out about tourism in the city of Padang. This design method uses descriptive qualitative and SWOT analysis approaches (Strength, Weakness, Opportunity, Threat) to find a solution to the problem at hand. In the preparation of content, observations, documentation and internet sources are carried out. The main media of the Hang Around Padang Guidebook Travel book is arranged in a simple and easy to understand style. Then supported by media stickers, bookmarks, posters, tote bags, bag markers, Instagram accounts and post cards.Keywords: Books, Travel Guide, Photography